2015
DOI: 10.1016/j.molmed.2015.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Three cheers for the goblet cell: maintaining homeostasis in mucosal epithelia

Abstract: Many organs throughout the body maintain epithelial homeostasis by employing a mucosal barrier which acts as a lubricant and helps to preserve a near-sterile epithelium. Goblet cells are largely responsible for secreting components of this mucosal barrier and represent a major cellular component of the innate defense system. In this review we summarize what is known about the signaling pathways that control goblet cell differentiation in the intestine, the lung, and the ocular surface, and we discuss a novel f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
132
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(143 citation statements)
references
References 107 publications
5
132
0
3
Order By: Relevance
“…Studies on the transcriptional regulation of intestinal lineage determination have identified the factors controlling goblet cell differentiation and maturation (McCauley and Guasch, 2015). Notch1 signaling drives epithelial progenitor cell specification to absorptive enterocytes and inhibits secretory cell differentiation via the Hes1 transcription factor (Fre et al, 2005; Jensen et al, 2000), whereas Notch1 inhibition results in robust conversion of proliferating crypt progenitors into terminally differentiated goblet cells (van Es et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the transcriptional regulation of intestinal lineage determination have identified the factors controlling goblet cell differentiation and maturation (McCauley and Guasch, 2015). Notch1 signaling drives epithelial progenitor cell specification to absorptive enterocytes and inhibits secretory cell differentiation via the Hes1 transcription factor (Fre et al, 2005; Jensen et al, 2000), whereas Notch1 inhibition results in robust conversion of proliferating crypt progenitors into terminally differentiated goblet cells (van Es et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Data from the studies in the gut and respiratory tree laid the foundation for study of conjunctival epithelial and goblet cell differentiation. A very helpful review of similarities and differences between goblet cell differentiation in the mucosal systems was recently published (McCauley and Guasch, 2015). …”
Section: Goblet Cell Differentiationmentioning
confidence: 99%
“…As goblet cells contribute to the maintenance of epithelium integrity, homeostasis, and modulation of immune responses (29,32,(39)(40)(41)(42)(43), the reduction in goblet cell numbers prompted us to determine whether HU alters intestinal barrier properties. We first examined the expression of one of the epithelial tight junction components, claudin 3, in the colon of HU and Ctrl mice.…”
Section: Altered Colonic Epithelial Cell Homeostasis In Hu Micementioning
confidence: 99%